2009
DOI: 10.1002/jor.20781
|View full text |Cite
|
Sign up to set email alerts
|

Systemic human minidystrophin gene transfer improves functions and life span of dystrophin and dystrophin/utrophin‐deficient mice

Abstract: Duchenne muscular dystrophy (DMD) is the most common and lethal genetic muscle disease, caused by mutations in the dystrophin gene. No efficacious treatment is currently available. Here we report AAV vector systemic delivery and therapeutic benefits of the functional human minidystrophin gene in a severe and more reliable DMD mouse model, the dystrophin/utrophin double deficiency mouse (dysÀ/À:utrnÀ/À, dKO). These mice show many pathologic and phenotypic signs typical of DMD in humans including kyphosis and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 28 publications
2
52
0
1
Order By: Relevance
“…Previous studies using mice have demonstrated that virusmediated transduction is a practical and efficient technique to deliver transgenes to mice. Systemic administration of rAAV vectors has repeatedly shown diaphragm transduction; however, the serotype, promoter, and animal model have resulted in a wide range of success (Gregorevic et al, 2004(Gregorevic et al, , 2008Yue et al, 2008;Wang et al, 2009;Yu et al, 2009;Kornegay et al, 2010). Regional delivery of rAAV has resulted in successful transduction of the murine diaphragm (Bish et al, 2008;Falk et al, 2013), and an alternative route using a gel-based delivery method directly administered to the diaphragm demonstrated high efficiency of gene transfer (Mah et al, 2004(Mah et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using mice have demonstrated that virusmediated transduction is a practical and efficient technique to deliver transgenes to mice. Systemic administration of rAAV vectors has repeatedly shown diaphragm transduction; however, the serotype, promoter, and animal model have resulted in a wide range of success (Gregorevic et al, 2004(Gregorevic et al, , 2008Yue et al, 2008;Wang et al, 2009;Yu et al, 2009;Kornegay et al, 2010). Regional delivery of rAAV has resulted in successful transduction of the murine diaphragm (Bish et al, 2008;Falk et al, 2013), and an alternative route using a gel-based delivery method directly administered to the diaphragm demonstrated high efficiency of gene transfer (Mah et al, 2004(Mah et al, , 2010.…”
Section: Discussionmentioning
confidence: 99%
“…5 The AAV capsid itself is a completely foreign protein and therefore a humoral immune response to vector administration was anticipated. Pre-existing humoral immunity to AAV was not an exclusion criterion in this study with the rationale that the relevance of in vitro assays of vector neutralization before i.m.…”
Section: Lack Of Cd8 Infiltration Into Injected Musclementioning
confidence: 99%
“…[4][5][6] Comprehensive proof of concept and preclinical testing has evaluated the effectiveness of AAV-minidystrophin gene delivery in animal models of DMD including the mdx mice and dystrophin/utrophin double knockout mice. Minidystrophin expressed after AAV delivery to dystrophin deficient models has been shown to: correctly localize to the sarcolemma, restore the missing dystrophin-associated protein complex to the cell membrane, ameliorate dystrophic pathology in mdx muscle, normalize myofiber morphology, normalize cell membrane integrity, restore missing dystrobrevin complex, partially restore α-syntrophin association with the cell membrane, partially restore nitric oxide synthase activity, reduce muscle fibrosis, reduce myofiber central nucleation, improve whole-body endurance and muscle force transduction, reduce kyphosis and limb deformation, and increase general health and lifespan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For immunofluorescent staining, hematoxylin and eosin staining (H&E), tissue samples were cryosectioned to a thickness of 7 mm and processed according to previous publications [20]. The transgene expression was measured according to the method described, and was normalized by inner control.…”
Section: Hande Staining and Capillary Densitymentioning
confidence: 99%